CONTEXTUAL EFFECT OF INTEGRATED HEATH POST ON NUTRITIONAL STATUS AMONG CHILDREN AGED 6-59 MONTHS IN SURABAYA, EAST JAVA - Aziza, Triana Ulfa Nur; Dewi, Yulia Lanti Retno; Pamungkasari, Eti Poncorini (Journal of Maternal and Child Health, 2020)
Background: A child will come into toddler phase which is the rapid growth and development phase. It turns children into one of the groups that vulnerable to suffer from undernutrition. The data of Riskesdas (Basic Health Research) in 2018 indicates that the percentage of malnutrition and undernutrition  in Indonesia is 17.7%, in which the number is still higher than the target of National Medium Term Development Plan 2019 which is 17%. The study aimed to analyzes factors that affect nutritional status of children aged 6 ? 59 months in Surabaya, East Java.Subjects and Method: This was a cross sectional study conducted at 25 integrated health posts (posyandu) in Surabaya, East Java, from August to September 2019. A sample of 200 children aged 6 ? 59 months was selected by stratified random sampling. The dependent variable was nutritional status (weight for age). The independent variables were history of exclusive breastfeeding, history of low birth weigth (LBW), maternal educational level, maternal knowledge, maternal occupation, family income, and environmental hygiene and sanitation. The data were collected by questionnaire and analyzed by a multiple logistic regression run on Stata 13.Results: Poor nutritional status increased with the history of LBW (b= 5.29; 95% CI= 1.87 to 6.72; p= 0.003) and poor environmental hygiene and sanitation (b= 3.35; 95% CI= 0.77 to 5.94; p= 0.011). Poor nutritional status decreased with maternal educational status ?Senior high school (b= -2.81; 95% CI= -5.24 to -0.38; p= 0.023), high maternal knowledge (b= -2.68; 95% CI= -5.01 to -0.35; p= 0.024), and high family income (b= -3.37; 95% CI= -6.04 to -0.71; p= 0.013).Conclusion: Poor nutritional status increases with the history of LBW and poor environmental hygiene and sanitation. Poor nutritional status decreases with maternal educational status ?Senior high school, high maternal knowledge, and high family income.Keywords: nutritional status, birth weight, sanitation, children under fiveCorrespondence: Triana Ulfa Nur Aziza. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir.Sutami 36A, Surakarta, Central Java, Indonesia. Email: trianaulfanuraziza@gmail.com. Mobile: +6281358396565Journal of Maternal and Child Health (2020), 5(1): 79-87https://doi.org/10.26911/thejmch.2020.05.01.09